PENGARUH KARAKTERISTIK AUDITOR INDEPENDEN DAN AFILIASI KANTOR AKUNTAN PUBLIK BEREPUTASI TERHADAP KUALITAS AUDIT - Anggreni Dian Kurniawati; Sisianti Dewi Putry; Cahyo Indraswono (Jurnal Akuntansi Dan Manajemen, 2022)
This study aims to provide empirical data about the impact of workload and auditor specialty, two independent auditor characteristics, on audit quality as well as the impact of affiliation with a reputable public accounting firm. In this study, absolute discretionary accruals using the Modified Jones technique are used as a proxy for audit quality. 129 manufacturing businesses registered on the Indonesia Stock Exchange for the years 2017 through 2020 comprise the sample for this study. Data from the Public Accounting Firm's 2017–2020 audited financial reports as well as PPPK data on the number of partners and clients are utilized. Purposive sampling was used to do the sampling. The study found that while the auditor specialization variable had no effect on audit quality, the workload variable had a positive effect on audit quality. The affiliation with a reputable public accounting firm has an effect on audit quality, however this study cannot prove it.